Tattooing amongst youth in Bloemfontein: skin deep communicative signs of a minority group? - Lombard, Elbie; Bergh, Luna (Department of Communication Science, University of the Free State, 2014)
This article reports on a research project that was undertaken to determine both the scope and communicative value of tattoos mainly among students of the University of the Free State (UFS) in Bloemfontein, South Africa. The owner of the tattoo shop on the Bloemfontein Campus of the UFS was interviewed, while clients of the tattoo shop as well as undergraduate Communication Science students, a larger random group of students and young working adults of the same age completed a questionnaire anonymously. The expectations were that tattoos among the four groups mentioned (i) would not be predominantly culturally determined, nor (ii) visible all the time; nor (iii) chosen specifically to communicate a rebellious message. In a follow-up study on the same campus, Communication Science students requested fellow students to complete a slightly adapted questionnaire as part of a class assignment. The findings of the analysis are evaluated in terms of both incremental and entity theories, against the background of a brief history of tattoos as a means of expressing identity. This study contributes to the understanding of the role tattoos play in expressing the identities of communities. The findings indicate that the participants choose tattoos for different reasons than a few decades ago in other parts of the world. It can also be concluded that tattoos are by no means skin-deep communicative signs. Given that the majority of respondents have tattoos, the tattoos cannot be considered the signs of a minority group.
Keywords: Tattoos; Minority group; Bloemfontein; South Africa; University of the Free State